Look Closer, Draw Better - Ewing, Kateri (Rockport Publishers, 2019)
Look Closer, Draw Better is a step-by-step technique book based on observational drawing by a noted American artist and author-written for advanced beginners and up, offering techniques in graphite, charcoal, ink, and watercolor wash.